Urban Design for MBTA Communities: Using Livability Analysis to Inform Design and Policy in Andover, MA - Collins, Anthony. (Tufts University. Tisch Library., 2024)
Thesis (M.A.)--Tufts University, 2024.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Christine Cousineau.; Committee: Scott Horsley.; Keyword: Urban planning.